Cardinal Purple for Maximilian of Pernstein. A Contribution to Aristocratic Women’s Political Communication (Theatrum historiae, 2019)
The aim of the study is to show what means and methods served noblewomen in the early modern period when communicating with the papal court. The studied issue will be analysed through the example of Maria Manrique de Lara, who at the beginning of the 1590s attempted to help her second-born son Maximilian of Pernstein work his way up to the College of Cardinals.
Keywords: political communication; Maximilian of Pernstein; gender history; cardinal’s elevation; Holy See; Habsburg dynasty; family network; client relations